Estimation of Prevalence of Musculoskeletal Pain & Rheumatic Disorders in a Rural Community of Bangladesh (Medicine Today, 2020)
Introduction: Rheumatic disorders are one of the largest health problems in the world both in developed & developing countries. They are the most common causes of chronic health problems and long term physical disability, work loss and loss of income. The study was conducted among the 15 plus years aged people in selected areas based on broad objective of exploring the prevalence of rheumatic disorders.Materials and Methods: It was an Observational cross sectional study. The study was conducted among the people of nineteen small villages of Sonargaon upazilla in Narayanganj district, Bangladesh. This study was conducted From January 2010 to December 2011. All subjects of the defined area aged  15 years were included in this study.Results: The point prevalence rate of definite rheumatic disorders was 23.7%. Age, sex and occupations were associated with the overall prevalence rate. The prevalence was higher (51.8%) in older aged (65years and above) population. Females (34.5%) were affected more than males (18.6%) in this rural area.Conclusion: These diseases are associated with some form of disability and work loss, as well as loss of income. More community- based studies with the design for the identification of associate’s factors for individual rheumatic disease are needed. So that appropriate messages can be given to the community for prevention and treatment of rheumatic disorders.Medicine Today 2020 Vol.32(1): 33-36